M [videorecording (DVD)] - Lang, Fritz, 1890-1976; Lorre, Peter; Widmann, Ellen; Landgut, Inge; Wernicke, Otto, 1893-1965; Loos, Theodor, 1883-1954; Friedkin, William; Chabrol, Claude, 1930-2010 (Criterion collection, 2004)
When a serial killer is stalking the children of the city, everyone, including the criminal underworld, wants to see him brought down. The story is based on the Düsseldorf child murders of 1929.